2022
DOI: 10.3389/fnins.2021.811080
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Hesperidin, Coumarin, and Deferoxamine Iron Chelation and Antioxidant Activity Against Excessive Iron in the Iron Overloaded Mice

Abstract: ObjectiveIron accumulation in the brain leads to the development of Alzheimer’s and Parkinson’s diseases. Nowadays, iron chelation therapy is the best way to decrease the side effects of iron and amyloid plaques accumulation. Iron chelators are commonly used for the treatment of Alzheimer’s disease. Previous studies have shown that natural products such as phenol and flavonoid compounds could chelate heavy metals. In the current study, we examined the iron chelation activity of hesperidin and coumarin on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…The results showed that hesperidin has more potential iron chelation activities compared to deferoxamine, a popular chelator for treatment of chronic iron overload [70]. The antioxidant activity of hesperidin exhibits also by reducing the production of reactive oxygen species and increasing the activities of antioxidant enzymes, catalase and superoxide dismutase [71,72]. It should be mentioned that hesperidin exhibits lower antioxidant activity in comparison to its aglycone form, alike other flavonoids [60].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The results showed that hesperidin has more potential iron chelation activities compared to deferoxamine, a popular chelator for treatment of chronic iron overload [70]. The antioxidant activity of hesperidin exhibits also by reducing the production of reactive oxygen species and increasing the activities of antioxidant enzymes, catalase and superoxide dismutase [71,72]. It should be mentioned that hesperidin exhibits lower antioxidant activity in comparison to its aglycone form, alike other flavonoids [60].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…A: negative control group (received normal saline), B: DFO-treated group (25 mg/kg/day DFO as i.p. injection), C: positive control group (iron-overloaded), D: DFO-treated iron-overload group (25 mg/kg/day), E: caffeic acid-treated iron-overloaded group (30 mg/kg/day), F: caffeic acid-treated iron-overload group (50 mg/kg/day), G: ferulic acid-treated iron-overload group (30 mg/kg/day), and H: ferulic acid-treated iron-overloaded group (50 mg/kg/day) (2,19,28,29). The dosage of ferulic acid was selected according to previous studies.…”
Section: Animal Study and Treatmentmentioning
confidence: 99%
“…DFO-treated mice received DFO (25 mg/kg/day; i.p.) four times a week for 4 weeks (2,8). Groups A and B received normal saline in the 3rd month.…”
Section: Animal Study and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations